The winds of change at Siemens - Salvador, Rita Alexandra Duarte Moura (2013)
Strategic change is a topic of great importance given the turbulence of the markets in which firms operate. Related to this topic, it has recently been developed the concept of dynamic capabilities, which refers to the ability of companies to sustain their competitive advantage in changing environments. Often as a mean to cope with the challenges presented by the environments, companies hire outside CEOs in order to acquire new perspectives, capabilities and mindsets to improve company’s performance. This dissertation comprises a teaching case about Siemens. The longstanding corporation has a history of success but where there were also some threats to the sustainability of the company in the market. In this case, the main focus is on the period since 2007. In that period, Siemens hired the first outside CEO in its history and the crisis took place, putting to the test the endurance of the CEO and, ultimately, of the company.